2013
DOI: 10.1155/2013/901740
|View full text |Cite
|
Sign up to set email alerts
|

No Association ofIFNG+874T/ASNP andNOS2A-954G/CSNP Variants with Nitric Oxide Radical Serum Levels or Susceptibility to Tuberculosis in a Brazilian Population Subset

Abstract: Tuberculosis (TB) is one of the most common infectious diseases in the world. Mycobacterium tuberculosis infection leads to pulmonary active disease in approximately 5–10% of exposed individuals. Both bacteria- and host-related characteristics influence latent infection and disease. Host genetic predisposition to develop TB may involve multiple genes and their polymorphisms. It was reported previously that interferon gamma (IFN-γ) and nitric oxide synthase 2 (NOS2) are expressed on alveolar macrophages from TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…In Brazil, the NOS2A-954G/C polymorphism have been reported in studies with tuberculosis and leprosy. In both studies, the allelic and genotypic frequencies were similar to the one found in this study, even though their population were from South and Southeast region [ 50 , 51 ]. Although no association has been found, this study is the first to report NOS2A-954G/C polymorphism and NO levels in malaria exposed individuals in endemic region of Brazil.…”
Section: Discussionsupporting
confidence: 82%
“…In Brazil, the NOS2A-954G/C polymorphism have been reported in studies with tuberculosis and leprosy. In both studies, the allelic and genotypic frequencies were similar to the one found in this study, even though their population were from South and Southeast region [ 50 , 51 ]. Although no association has been found, this study is the first to report NOS2A-954G/C polymorphism and NO levels in malaria exposed individuals in endemic region of Brazil.…”
Section: Discussionsupporting
confidence: 82%
“…In spite of the interaction of Mtb with TLRs leads to phagocyte activation, the interaction itself does not lead to immediate ingestion of the mycobacteria (Kleinnijenhuis et al, 2011). Host genetic may involve multiple genes and their polymorphisms to develop TB (Leandro et al, 2013). TLR association may differ from population to another.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium bovis ( M. bovis ) is the main causative agent of bovine tuberculosis (bTB), a disease of great concern in many countries, including England, Ireland, Brazil, China and Taiwan, for its detrimental economic impact and its effect on humans [ 3 , 4 , 8 , 13 , 16 , 18 ]. The worldwide prevalence of bTB remains a significant economic burden, with annual losses of approximately 3 billion US dollars [ 1 ].…”
mentioning
confidence: 99%
“…Previous studies suggest that certain host genetic variants contribute to tuberculosis susceptibility [ 1 , 2 , 3 , 4 ]. Several candidate proteins associated with the susceptibility, including nitric oxide synthase 2 inducible gene ( NOS2 ), tumor necrosis factor α ( TNF-α ), solute carrier family 11 member 1 ( SLC11A1 ), vitamin D receptor ( VDR ) and toll-like receptors ( TLRs ), have been investigated for their possible associations between genetic variants and tuberculosis susceptibility [ 11 , 15 , 16 , 18 , 19 , 23 , 31 , 35 ]. The inducible nitric oxide synthase (iNOS) which is encoded by the NOS2 gene is a cytoplasmic protein and absent in resting cells, but is rapidly produced in response to stimuli, such as infections and cytokines [ 6 , 12 , 21 ].…”
mentioning
confidence: 99%